Dissociative and Analgesic Properties of Ketamine Are Independent. (November 2020) - Gitlin, Jacob; Chamadia, Shubham; Locascio, Joseph J.; Ethridge, Breanna R.; Pedemonte, Juan C.; Hahm, Eunice Y.; Ibala, Reine; Mekonnen, Jennifer; Colon, Katia M.; Qu, Jason; Akeju, Oluwaseun
Abstract : Background: Ketamine is a dissociative anesthetic with analgesic properties. Ketamine's analgesic properties have been suggested to result from its dissociative properties. To the authors' knowledge, this postulate is unsubstantiated. The authors hypothesize that the dissociative and analgesic properties of ketamine are independent. Methods: The authors conducted a single-site, open-label study of ketamine anesthesia (2 mg/kg) in 15 healthy subjects. Midazolam was administered at a prespecified time point to attenuate dissociation. The authors longitudinally assessed precalibrated cuff pain intensity and quality using Patient-Reported Outcomes Measurement Information System questionnaires, and dissociation, using the Clinician Administered Dissociative States Scale. Mixed effects models were used to assess whether dissociation accounted for the effect of ketamine on pain intensity and quality. Results: The dissociation model demonstrated an inverted U-shaped quadratic relationship between time and dissociation scores. Additive to this effect, midazolam reduced the dissociation adjusted means by 10.3 points (95% CI, 3.4 to 17.1; P = 0.005). The pain intensity model also demonstrated a U-shaped quadratic relationship between time and pain intensity. When the pain intensity model was reanalyzed with dissociation scores as an additional covariate, the dissociation term was not retained in the model, and the other effects were preserved in direction and strength. This result was conserved for nociceptive and neuropathic pain quality. Conclusions: Ketamine's analgesic properties are not exclusively caused by dissociation. Thus, ketamine may be used as a probe to advance our knowledge of dissociation independent neural circuits that encode pain. Abstract : The hypothesis that the dissociative and analgesic properties of ketamine are independent was tested in healthy subjects that received 2 mg/kg ketamine, and then, 2 mg of midazolam at a later timepoint. Ketamine-induced analgesia had no strong inherent relationship with ketamine-induced dissociation beyond being independently modulated by ketamine.Supplemental Digital Content is available in the text.